Antecedents of Customer Brand Engagement Affecting Customer Satisfaction, Trust, and Commitments in Forming Loyalty and Word of Mouth in Indonesia - Lestari, Unik D; Syah, Tantri Yanuar R (UI Scholars Hub, 2022)
Manuscript type: Research Article Research Aims: The research objective was to determine customer brand engagement (CBE) drivers, which directly or indirectly generate word of mouth (WOM) on Instagram through trust, commitment, customer satisfaction, and loyalty. Design/methodology/approach: This research was conducted in Indonesia with 213 respondents who are active on Instagram accounts, have an age range between 20 and 60 years, and have an attachment to products from middle to upper-class brands in Indonesia. This quantitative research uses the Structural Equation Model (SEM) method. Research Findings: The results show that customer involvement and flow experience are the main drivers of CBE, which then directly generate WOM, customer trust, and customer commitment. CBE also indirectly forms WOM through trust and commitment. Theoretical Contribution/Originality: This study can explain the importance of customer involvement and experience in forming CBE to gain loyalty and word of mouth through Instagram in Indonesia. Practitioner/Policy Implication: The managerial implication of the research is about brand-building strategies, forming satisfaction, trust, and commitment to brand loyalty in the short and long term through disseminating information on social media such as Instagram. Research limitation/Implications: This study has limitations; first, the research data only relies on one social networking site (Instagram) in Indonesia to test hypotheses. Second, the survey was about middle-class and above-class product brands. Third, in this case, it has not discussed demographics about age.